2011
DOI: 10.1158/1078-0432.ccr-10-2011
|View full text |Cite
|
Sign up to set email alerts
|

Phase II, Open-Label Study of Brivanib as First-Line Therapy in Patients with Advanced Hepatocellular Carcinoma

Abstract: Purpose: Brivanib, a selective dual inhibitor of fibroblast growth factor and VEGF signaling, has demonstrated encouraging antitumor activity in preclinical and phase I studies. We performed a phase II open-label study of brivanib as first-line therapy in patients with unresectable, locally advanced, or metastatic hepatocellular carcinoma.Experimental Design: Brivanib was administered orally at a dose of 800 mg once daily. The primary objective was 6-month progression-free survival, progression-free survival r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
97
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(101 citation statements)
references
References 29 publications
2
97
0
2
Order By: Relevance
“…The FGFR inhibitor that has been most extensively studied in patients with HCC is brivanib, an ATP-competitive dual inhibitor of VEGFR and FGFR1-3 (24). Despite strong preclinical and phase II data of HCC (25,26), brivanib failed in large randomized phase III trials in both the first-and second-line settings for patients with advanced HCC (27,28). Nonetheless, FGFR inhibition remains an attractive therapeutic target for HCC, and requires further investigation of its possible clinical applications.…”
Section: Discussionmentioning
confidence: 99%
“…The FGFR inhibitor that has been most extensively studied in patients with HCC is brivanib, an ATP-competitive dual inhibitor of VEGFR and FGFR1-3 (24). Despite strong preclinical and phase II data of HCC (25,26), brivanib failed in large randomized phase III trials in both the first-and second-line settings for patients with advanced HCC (27,28). Nonetheless, FGFR inhibition remains an attractive therapeutic target for HCC, and requires further investigation of its possible clinical applications.…”
Section: Discussionmentioning
confidence: 99%
“…Although an overall survival time of 9.8 mo was observed in a phase Ⅱ study [85] , sunitinib did not outperform sorafenib in a phase Ⅲ randomized study (overall survival, 8.1 and 10.0 mo, respectively; P = 0.0019) [86] . Brivanib, a selective dual inhibitor of fibroblast growth factor (FGF) and vascular endothelial growth factor (VEGF) signaling, was associated with a median overall survival of 10 mo in a phase Ⅱ trial [87] and was considered a promising new drug for advanced HCC. However, the primary endpoint of brivanib not being non-inferior to sorafenib was not met in a subsequent phase Ⅲ trial (overall survival, 9.5 and 9.9 mo, respectively, P value is nonsignificant) [88] .…”
Section: Molecular Target Therapiesmentioning
confidence: 99%
“…On the other hand, brivanib, which targets VEGFR, PDGFR and FGFR, also failed to prolong OS (Table 1) in a phase III trial conducted to investigate its efficacy as a first line therapy even though it had a more favorable toxicity profile than sorafenib [89,90]. Moreover, another phase III, randomized, placebo-controlled study investigated the efficacy of brivanib after sorafenib failure and the authors reported that, in comparison to placebo, brivanib resulted in a longer median TTP but insignificant increase in the OS (Table 1) [91][92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108].…”
Section: Anti-angiogenic Agentsmentioning
confidence: 99%